Bird extinctions threaten to cause disproportionate reductions of functional diversity and uniqueness - Ali,JR; Blonder,BW; Pigot,AL; Tobias,JA (Functional Ecology, 2023)
1. Human activities are driving rapid defaunation of Earth's ecosystems throughincreasing rates of extinction. However, the ecological consequences of spe-cies loss remain unclear, in part due to the limited availability of high-resolutionfunctional trait data.2. To address this, we assess how predicted extinctions will reshape avian func-tional diversity quantified using a multidimensional trait space, or morphospace,reflecting variation in eight key morphological traits closely linked to ecologicalfunction across 9943 (>99%) extant bird species.3. We show that large regions of this morphospace are represented by very fewspecies and, thus, vulnerable to species loss. We also find evidence that speciesat highest risk of extinction are both larger and functionally unique in terms ofecological trait dimensions unrelated to size, such as beak shape and wing shape.4. Although raw patterns suggest a positive relationship between extinction riskand functional uniqueness, this is removed when accounting for phylogeny andbody mass, indicating a dominant role for clade- specific factors, including thecombination of larger average body size and higher extinction risk in the non-passerine clade.5. Regardless of how a threat is related to uniqueness, we show using simulationsthat the loss of currently threatened bird species would result in a greater loss ofmorphological diversity than expected under random extinctions.6. Our results suggest that ongoing declines of threatened bird species may drivea disproportionately large loss of morphological diversity, with potentially majorconsequences for ecosystem functioning.K E Y W O R D Sextinction, functional redundancy, functional traits, hypervolume, morphological diversity,threatened species, trait space, uniqueness